Systematic evaluation of neuro-ophthalmic outcomes of the ophthalmic artery covered by flow-diverter - Ma, Yu-Hu; He, Yong-Lin; Lin, Sen; Pan, Ya-Wen; Zhang, Chang-Wei (Frontiers in Neurology, 2025)
Carotid-ophthalmic aneurysms (COA) are complex and severe intracranial arterial lesions, and their treatment and management have always been a focus of clinical research. In recent years, the introduction of flow diverters (FD) has provided a revolutionary method for the treatment of intracranial aneurysms (IA). Although FD has achieved significant success in reducing the risk of COA rupture, the complex anatomical structure and critical function of the ophthalmic artery (OphA) mean that covering the OphA with FD may lead to adverse ophthalmic outcomes. This review aims to systematically examine the ocular complications and their mechanisms when FD covers the OphA in the treatment of COA, emphasizing the potential risks that clinicians should be aware of when applying FD treatment, to reduce complications and improve the overall prognosis of patients.